2007 IEEE Wireless Communications and Networking Conference 2007
DOI: 10.1109/wcnc.2007.351
|View full text |Cite
|
Sign up to set email alerts
|

Path Loss Measurements in Sea Port for WiMAX

Abstract: Large scale path loss measurements in sea port are presented. This investigation is useful before deploying Worldwide Interoperability for Microwave Access (WiMAX) equipments to provide last mile Broadband Wireless Access (BWA) for ships and boats in the sea port. Measurements were carried out at 5.8 GHz. Two-ray model fits measured large scale path loss reasonably well. When the distance is very large, the received signal was found to attenuate at the rate of more than double of that of the free space. The at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…One possible approach to gain knowledge about the wireless propagation channel is to conduct channel measurement campaigns. In the recent years some channel measurement campaigns were performed for maritime scenarios [1], [2], [3], [4], [5], [6], [7], [8]. However, these measurements were conducted with small bandwidth (maximum 20 MHz) and therefore, with low delay-resolution.…”
Section: Introductionmentioning
confidence: 99%
“…One possible approach to gain knowledge about the wireless propagation channel is to conduct channel measurement campaigns. In the recent years some channel measurement campaigns were performed for maritime scenarios [1], [2], [3], [4], [5], [6], [7], [8]. However, these measurements were conducted with small bandwidth (maximum 20 MHz) and therefore, with low delay-resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in the implementation of mobile radio system in the 5 GHz band [9][10][11][12]. As compared to the lower frequency (< 2 GHz) applications in [3,4], high-speed or highcapacity wireless applications can be achieved at 5 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the lower frequency (< 2 GHz) applications in [3,4], high-speed or highcapacity wireless applications can be achieved at 5 GHz. For example, high-speed WiMAX at 5.8 GHz was studied in [9], and microwave landing system at 5 GHz was examined in [11,12]. It has been shown that the 5 GHz band has a good potential for military applications [13], such as off-shore anti-terrorist surveillance or application of unmanned surface vehicles (USVs) in the maritime environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further works in this field have been done in urban and suburban environments [5], [6]. Besides, although [7], [8] and [9] present experimental measurements of propagation characteristics for maritime radio links, they do not apply to conditions covered by our study. To the best of the authors' knowledge, buoy-to-ship path loss characteristics over sea at 5.8 GHz near urban environments have not been investigated.…”
Section: Introductionmentioning
confidence: 99%